Beyond-Mild Psoriasis: A Consensus Statement on Calcipotriol and Betamethasone Dipropionate Foam for the Topical Treatment of Adult Patients - Aschoff, Roland; Bewley, Anthony; Dattola, Annunziata; De Simone, Clara; Lahfa, Mourad; Llamas-Velasco, Mar; Martorell, Antonio; Pavlovic, Mira; Sticherling, Michael (Dermatology and Therapy, 2021)
Introduction There are clear treatment options for mild psoriasis where topical therapies are the mainstay, and for severe psoriasis where systemic therapy (biologic or non-biologic) is necessary. However, there is less clarity in the 'grey zone' of patients in the moderate or so-called 'beyond-mild' segment. There are frequent delays to the initiation, discontinuation, switching and dose change in treatment, and many patients fail to continue treatment because of concerns about safety or lack of efficacy. Treatment with topical therapies, such as calcipotriol and betamethasone dipropionate (Cal/BD) combinations, may be suitable for these patients. Method These consensus recommendations on the use of topical therapies including Cal/BD foam for beyond-mild psoriasis originated from a modified Delphi process of European clinical experts. In the process, the experts iteratively refined a series of draft statements, which had to receive >= 80% approval to be incorporated into the consensus. Results The experts identified three main themes: Cal/BD foam as monotherapy, as an add-on to non-biologic systemic therapies and as an add-on to systemic biologics. The consensus emphasises disease factors and patient preference in treatment choice, summarises the evidence base for Cal/BD foam monotherapy for flare treatment as well as long-term management, and identifies the potential for improved treatment outcomes, such as reduced time to onset of action and reduced systemic dose to minimise side effects for add-on Cal/BD therapy to non-biologic systemics. The recommendations regarding add-on Cal/BD foam to biologics are similar to those for non-biologic systemic therapies, but also include suggestions for patients on biologics who are late responders. As clinical choices of Cal/BD combination vary, we have here often used 'Cal/BD' without reference to any particular formulation. Conclusions These recommendations aim to give practical guidance to those treating patients with beyond-mild psoriasis, to support patients' use of topical preparations and to optimise treatment outcomes.
CRIS-Team WoS Importer:2021-09-24